Complement Inhibition Alleviates Cholestatic Liver Injury Through Mediating Macrophage Infiltration and Function in Mice - Guo, Zhenya; Chen, Junze; Zeng, Yonglian; Wang, Zefeng; Yao, Mei; Tomlinson, Stephen; Chen, Bin; Yuan, Guandou; He, Songqing (Frontiers in Immunology, 2022)
Background and aims Cholestatic liver injury (CLI) is a serious risk factor for postoperative complications. Studies have demonstrated that CLI depends upon inflammatory reaction and oxidative stress. Complement system is involved in a wide range of liver disorders, including cholestasis. In this study, our focus was to determine the role of complement and therapeutic effect of site-targeted complement inhibitor CR2-Crry in CLI. Methods Wild-type or complement gene deficient mice were sham-operated or subjected to common bile duct ligation (BDL) to establish CLI mouse models. These models were intervened by using CR2-Crry or GdCl3. Through biochemical analysis, flow cytometry, immunohistochemistry, ELISA, quantitative RT-PCR and other methods, the role of complement and the potential therapeutic effect of CR2-Crry were investigated. Results C3 deficiency or CR2-Crry could significantly reduce liver injuries in CLI mouse model, and remarkably inhibit the number of neutrophils and macrophages in the liver. C3 deficiency or CR2-Crry could significantly reduce the expression of Mac-1 on neutrophil and VCAM-1 in liver tissue. More importantly, C3 deficiency or CR2-Crry could significantly inhibit M1 macrophage polarization in CLI mouse model. After intravenous injection of GdCl3, the infiltration and activation of macrophages were inhibited, however, the liver injury increased significantly. After BDL, the level of LPS in portal blood increased significantly, rather than in peripheral blood. After GdCl3 treatment, LPS in peripheral blood increased significantly, implicating the potential role of macrophages in clearing the portal blood LPS. Oral administration of ampicillin could decrease the level of LPS in portal blood and alleviate the liver damage in GdCl3 treated mice. In contrast, intraperitoneal injection of LPS could increase the portal blood LPS and reverse the protective effect of ampicillin. Interestingly, C3 deficiency does not affect the clearance of LPS. Conclusions Complement was involved in CLI, which may through mediating the infiltration and activation of neutrophils and macrophages in the liver by regulating the expression of Mac-1 and VCAM-1. C3 deficiency or CR2-Crry could significantly alleviate CLI. Inhibition of complement could preserve the protective function of macrophages in clearing LPS, indicating that complement inhibition would be an ideal therapeutic strategy for the treatment of CLI.